DEVELOPMENT OF DC-DC BUCK CONVERTER FOR SOLAR PANEL ENERGY STORAGE THROUGH LOAD OPTIMIZATION AND FEEDBACK CIRCUIT - Widyaningrum Indrasari; Gusti Rama; Rahmondia Nanda Setiadi; Lilik Hasanah; Siti Kudnie Sahari (Spektra: Jurnal Fisika dan Aplikasinya)
Solar panels are crucial components in converting sun radiation into electrical energy through the photovoltaic effect. A solar panels cannot be connected directly to the load due to its low energy conversion efficiency and low output voltage. One of the methods used to control solar cells to operate efficiently at their maximum power point is MPPT. In this paper, we design a DC-DC converter by modifications of the Butterworth filter circuit and feedback circuit in the MPPT system for storing solar panel electrical using the Hill Climbing (HC) method. The device consists of a DC-DC buck converter circuit, two pieces of INA219 sensors, a DS18B20 temperature sensor, a MAX44009 light intensity sensor, a SD card module and a DS3231 RTC. The DC-DC buck converter circuit simulation is carried out to determine the optimal load. The load optimization was conducted by analyzing the AC simulation using Ltspice software. The magnitude of the output voltage ripple in nine different loads was observed.  From the simulations performed, it was found that the 50 Ω load has an output voltage ripple of 8.96 mV and is smaller than the other loads. The main DC-DC buck converter circuit is designed using a butterworth low pass filter with a cut-off frequency of 1000 Hz (R = 50 Ω, L = 33.8 mH and C = 750 nF) and a feedback circuit with a cut-off frequency of 500 Hz is added. From the prototype measurement, it was found that the average output power was 3249,7 milliwatts and the average input power was 4779 milliwatts, thus the average efficiency was 68%. With these results, the DC-DC converter circuit configuration is suitable for use in electrical energy storage systems from solar panels that have high efficiency.